OC-016 Sequential activation of CXCR3 and CCR6 mediates recruitment and positioning of interleukin 17 producing T cells in the liver. (23rd September 2015) - Oo, Y H; Banz, V M; Kavanagh, D; Withers, D R; Humphreys, E; Lee-Turner, L; Reynolds, G; Kalia, N; Hubscher, S G; Eksteen, B; Adams, D H
Abstract : Introduction: IL-17 secreting CD4 T cells (Th17) are a distinct lineage of pro-inflammatory lymphocytes that develop under control of the transcription factor RORγt. Th17 cells are pathogenic in models of autoimmunity and have been implicated in the pathogenesis of several forms of liver inflammation including primary biliary cirrhosis, alcoholic and viral hepatitis. Despite their importance in perpetuating inflammation, there is little known about the molecular basis for their recruitment and positioning to specific sites such as the liver. Methods: Human intrahepatic Th17 cells were isolated from explanted liver tissue without cytokine expansion and analysed by multi colour flow cytometry. Murine liver injury models of Con A hepatitis, MCD Diet and repeated CCL4 injections were used for intravital microscopic assessment of Th17 cell recruitment to the liver. Results: Less that 0.25% of T cells in normal human liver expressed IL-17 but we detected IL-17 secreting cells in inflamed human liver samples with the highest frequencies detected in patients with seronegative fulminant hepatitis (median 3.7%; IQR 3.4–3.9) non-alcoholic steatohepatitis (median 3.3%; IQR 2.7–3.5%) and auto-immune hepatitis (median 2.8%; IQR 2.6–3.3%). Intrahepatic IL-17+ cells expressed RORγt and the IL-23 receptor consistent with a Th17 lineage. They secreted IL-22 and IFNγ in addition to IL-17 and expressed high levels of the chemokine receptors CCR5, CCR6, CXCR3 and CXCR6. Intravital microscopy in murine models of acute liver injury (con-A hepatitis), steatohepatitis (MCD) and chronic liver injury (CCl4) demonstrated enhanced recruitment of adoptively transferred Th17 cells to the hepatic parenchyma via the sinusoids. Recruitment was significantly reduced by a blocking the CXCR3 ligand CXCL10 which also ameliorated liver injury. The CCR6 ligand, CCL20, was restricted to biliary epithelium and secreted by cholangiocytes in vitro suggesting a further recruitment signal positions Th17 cells near bile ducts in portal tracts. Conclusion: Th17 cells are recruited to sites of inflammation in the liver by sequential interactions in which the CXCR3 ligand, CXCL10 promotes recruitment into the parenchyma from blood via the sinusoids and the CCR6 ligand, CCL20 positions cells at the biliary epithelium.